Kyai Arsantaka: Tonggak Berdirinya Purbalingga serta Warisan dan Pengaruhnya hingga Kini - nur adila, amalia syifana (Universitas Negeri Semarang, 2025)
This article discusses the role of Kyai Arsantaka, who is considered one of the key figures in the formation of Purbalingga, a region in Central Java. As a revered historical figure, Kyai Arsantaka made significant contributions to the spread of Islamic teachings, as well as in establishing the social and cultural foundations of Purbalingga. Beyond his religious endeavors, his contributions can also be seen in infrastructure development, the strengthening of local traditions, and fostering harmonious social relationships within the community. This article explores the enduring legacy of Kyai Arsantaka spiritually, socially, and culturally which continues to be felt to this day. With a historical and anthropological approach, it provides an in-depth analysis of how the values championed by Kyai Arsantaka remain relevant and serve as guiding principles in the lives of the people of Purbalingga today.